The Higher Sensitivity of GABAergic Compared to Glutamatergic Neurons to Growth-Promoting C3bot Treatment Is Mediated by Vimentin - Adolf, Andrej; Turko, Paul; Rohrbeck, Astrid; Just, Ingo; Vida, Imre; Ahnert-Hilger, Gudrun; Höltje, Markus (Frontiers in Cellular Neuroscience, 2020)
The current study investigates the neurotrophic effects of Clostridium botulinum C3 transferase (C3bot) on highly purified, glia-free, GABAergic and glutamatergic neurons. Incubation with nanomolar concentrations of C3bot promotes dendrite formation as well as dendritic and axonal outgrowth in rat GABAergic neurons. A comparison of C3bot effects on sorted mouse GABAergic and glutamatergic neurons obtained from newly established NexCre;Ai9 x VGAT Venus mice revealed a higher sensitivity of GABAergic cells to axonotrophic and dendritic effects of C3bot in terms of process length and branch formation. Protein biochemical analysis of known C3bot binding partners revealed comparable amounts of beta1 integrin in both cell types but a higher expression of vimentin in GABAergic neurons. Accordingly, binding of C3bot to GABAergic neurons was stronger than binding to glutamatergic neurons. A combinatory treatment of glutamatergic neurons with C3bot and vimentin raised the amount of bound C3bot to levels comparable to the ones in GABAergic neurons, thereby confirming the specificity of effects. Overall, different surface vimentin levels between GABAergic and glutamatergic neurons exist that mediate neurotrophic C3bot effects.